Software development and management problem analysis of investment portfolio structure - Голоскоков, Олександр Євгенович; Воробйова, Анна Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of investors in the modern Ukrainian stock market is considered. Each investor faces a dilemma, wishing to have more yield and less risk. Since this task is controversial, the investor must make a compromise choice between yield and risk. The problem is that to be successful an investor needs help to assess the overall situation in the market. So far, there are so many online agencies, specialized in training to work with the securities market, but there is no the software that would allow to conduct investment portfolio management based on various mathematical models. Many people are involved in this area of the market, therefore; there is the need to automate securities transactions. It was proposed to consider methods for finding the risky structure of the portfolio and the allocation of available capital between the risky and nonrisky part of the portfolio using Markowitz models and Pontryagin’s max i mum principle, with the aim to develop an optimal reallocation strategy of investor funds. In carrying out this work, risky portfolio structure, found by maximizing the Sharpe relationship and based on the Markowitz portfolio theory, namely, the search for the minimum risk portfolio was determined. During the capital allocation between risky and nonrisky part of the portfolio, management in the form of feedback was used. All the calculations were made using the developed software and have allowed to evaluate the usefulness of the work. Research results and developed software can be used in investment departments of commercial banks and by small investors.